2021
DOI: 10.1108/ijqrm-06-2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of barriers of cyber-physical system adoption in small and medium enterprises using interpretive ranking process

Abstract: PurposeThe purpose of this paper is to report a study on analysis of barriers for cyber-physical system (CPS) adoption in small and medium enterprises (SMEs).Design/methodology/approachIn Industry 4.0 scenario, Indian SMEs are struggling to bring their manufacturing processes in line with large manufacturing sector. CPS is considered as the backbone of Industry 4.0, and its implementation in SMEs will make significant changes pertaining to manufacturing automation. However, due to the lack of a proper CPS impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These techniques only consider one type of variable and establish the interrelationship by doing the comparison among the variables with each other. Wankhede and Vinodh (2021) observed that the IRP has been used as an alternative ranking approach, specifically in lean manufacturing, supply chain management, manufacturing practices, etc. In this study, authors provide a comparative interpretation of ISM and IRP approaches and shows that the IRP gives more detailed hierarchical representation than the ISM, since it goes one step further to include the relationship of lean practices with respect to performance dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques only consider one type of variable and establish the interrelationship by doing the comparison among the variables with each other. Wankhede and Vinodh (2021) observed that the IRP has been used as an alternative ranking approach, specifically in lean manufacturing, supply chain management, manufacturing practices, etc. In this study, authors provide a comparative interpretation of ISM and IRP approaches and shows that the IRP gives more detailed hierarchical representation than the ISM, since it goes one step further to include the relationship of lean practices with respect to performance dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…The approach has been applied in the literature for the analysis of factors and barriers. Wankhede and Vinodh (2021) analyzed barriers to cyber-physical system (CPS) adoption in small and medium enterprises using the IRP method and developed a model showing a hierarchy of CPS barriers. Bhadu et al (2021) analyzed lean implementation barriers in Indian ceramic industries.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability 2022, 13, x FOR PEER REVIEW 25 of 36 13. Managers expect these technologies to evolve and/or enhance real-time "Capture/measure" of information relating to the status and performance of the production system.…”
Section: % 42%mentioning
confidence: 99%
“…Sustainability 2022, 13, x FOR PEER REVIEW 29 of 36 13. At the level of the "Capture/measure" step of the decision-making process, the use of artificial intelligence is less relevant or more restrictive to implement than big data analysis.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation